Clinical Utility of Human Papillomavirus ctDNA for Treatment Monitoring and Recurrence Prediction in Locally Advanced Cervical Cancer: A Systematic Review - Dilfuza Mirzaeva; Sharodiya Das; Laziz Y.T. O'g'li; Djurayeva Z. Baratovna; Dilshod Tolibov; Xalmuxamedov B. Taxirovich; Dilorom Dinmukhammadieva; Sourav Bhattacharjee (Indian Journal of Medical and Paediatric Oncology, 2026)
Abstract Locally advanced cervical cancer (LACC), defined as FIGO 2018 stages IB3-IVA, is associated with relapse rates between 30 and 60% after definitive chemoradiotherapy (CRT). The current strategy for monitoring is based on physical examinations and imaging, which could be confounded by radiation-induced fibrosis, and existing biomarkers like squamous cell carcinoma antigen lack sensitivity in detecting minimal residual disease (MRD). Circulating tumor DNA derived from human papillomavirus (HPV ctDNA) has recently been shown to be useful for molecular surveillance through liquid biopsies. This article aims to investigate the clinical significance of HPV ctDNA in monitoring the response to therapy and predicting recurrence in patients with LACC. This study is a systematic review of Scopus and PubMed databases (2017–2026) of articles examining the longitudinal detection of HPV ctDNA as a molecular marker in patients with LACC undergoing definitive CRT. Studies utilizing sensitive molecular techniques such as droplet digital polymerase chain reaction and next-generation sequencing were included and analyzed outcomes including MRD, recurrence, and survival. A total of seven papers were selected, utilizing results from large-scale cohort studies, such as CALLA Phase III trial and BioRAIDs trial conducted in Europe. The detection rate of HPV ctDNA at the time of diagnosis was 60.8 to 98.9%, correlating with tumor burden, defined by FIGO staging and nodal disease. The persistence of ctDNA at the end of treatment or 3 months following CRT as evidence of MRD consistently indicated a worse prognosis in terms of relapse. ctDNA positivity predicted worse progression-free survival (hazard ratio: 2.53–14.25) and predated radiographic relapse by 5.5 to 10 months. HPV ctDNA may serve as a promising adjunctive biomarker for MRD detection and early relapse prediction in LACC.